Little Brother-Big Brother Relationship through Malaysia-Indonesia Sosek-Malindo Initiatives: A Case Study of Entikong-Tebedu Border - Abdullah, Mohd Kamarulnizam; Anuar, Abdul Rahim; Eby Hara, Abubakar; Anwar, Mohammad Syafi’i (Serials Publications Pvt. Ltd., 2018)
Cross-border trade between two neighbouring countries reflects socioeconomic ties between border communities. As such, this paper examines the socio-economic development of communities at the border of Entikong (Kalimantan Barat, Indonesia) and Tebedu (Sarawak, Malaysia). Development undertaken by the respective governments, through the Sosek-Malindo platform, reflects to a certain extent, the concept of a Little Brother-Big Brother relationship, in which each intends to provide assistance through development projects that benefit both communities through employment creation and income generation. This can improve their socio-economic level that has been trapped in poverty and underdevelopment.